Can values of honesty, hard work, loyalty and discipline predict entrepreneurial orientation of Muslim owner managers? / Rohani Mohd ... [et al.] - Kamaruddin, Badrul Hisham; Yahya, Khulida Kirana (Faculty of Business and Management, 2015)
The purpose of the present study is twofold: first, to investigate the true values of Muslim owner managers; second, to examine the impact of these values on entrepreneurial orientations of Muslim small-scale entrepreneurs. 850 Muslim owner managers were selected randomly using the sampling frame provided by MajlisAmanah Rakyat Malaysia (MARA). 162 completed questionnaires were collected and analyzed. For this paper only two dimensions of entrepreneurial orientations were analyzed: proactive orientation and innovative orientation. Interestingly, the findings revealed that Muslim businessmen/women are honest, loyal, disciplined and hard working. Loyalty and honesty are positively related to proactive orientation, while discipline and hard-work are positively related to innovative orientation. The findings provide implications for existing relevant theories, policy makers, practitioners and learning institutions.